Leveraging digital media for brand awareness and engagement: a case study of Marico's digital marketing strategy - Neha, Tafriha Kamrul (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.